Different Isolate Comparison of Alternaria alternata in their pathogenisity ability and molecular Diagnosing - جفات مريم حسين; محمد بان طه; عبد المحسن رجاء غازي (Journal of Kerbala for Agricultural Sciences, 2015)
Series of Laboratory experiment were conducted at the Department of plant protection ,College of Agriculture ,University of Kerbala. Fours fungal isolate designated here after by AM1 , AM2 , AB and AK of Alternaria alternata were studied . show that more pathogenic isolate was AM2 , germination percentage of the cress seeds and tomatoes was 0.0% for both , inhibition percentage was 100%. Then , in A.B isolate, germination percentage of the cress seeds was 4.4% and tomatoes 0.0% and inhibition percentage was 49.97% , 100% respectively. Then ,in A.M1 isolate, germination percentage of the cress seeds and tomatoes were 8.86% and 73.33% respectively, while the inhibition percentages of the cress seeds and tomatoes were 89.87% 22.9% respectively. The less pathogenic isolate was AK , the germination percentages of the cress seeds and tomatoes were 60.0% and 83.66% respectively and the inhibition percentages of the cress seeds and tomatoes were 31.42% and 12.12% respectively. where other isolate were less pathogenitic on the seed .these isolates were diagnosed by using PCR technique which were molecularly similar.